Creating win-win situations for scientists: Gender and technical scientists working together - Kinati, Wole (International Livestock Research Institute, 2016)
Usually at the design stage of research programmes, technical researchers appreciate the integration of gender. But when it comes to field activities, the time and money needed to conduct research with a gender lens are seen as a constraint. Technical scientists tend to put aside some gender aspects during fieldwork. An example: in the research design, gender aspects were well-integrated in the tools and protocols. But in the field, the protocol to collect age- and gender-disaggregated data was not followed consistently. The information was collected with a different methodology from one location to the other, making it difficult to analyse the data. Social and technical scientists do not appreciate the same type of information. They need to work jointly to improve the livelihoods of the poor. Interview with Wole Kinati (ICARDA) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684